we can rearrange the equation as x^2+2*x*1+1^2=0

now, as we may know that (a+b)^2=a^2+2ab+b^2

so the above equation becomes (x+1)^2=0

now taking square root on both sides

x+1=0

subtracting 1 from both sides

x+1-1=0-1

or, x=-1

so the solution is x=-1

x^2 + 2x + 1 = 0

x^2 + x + x + 1 = 0

x(x + 1) + 1(x + 1) = 0

(x + 1)(x + 1) = 0

x = - 1 , x = - 1

Now

will be satisfied for only x = - 1

(- 1)^2 + 2(-1) + 1 = 0

1 - 2 + 1 = 0

2 - 2 = 0

0 = 0

Satisfied

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up